Systemic alterations and different tissue response to bioactive materials - Dal Fabbro, Renan [UNESP]; Cosme-Silva, Leopoldo [UNESP]; Benetti, Francine [UNESP]; De Araújo, Gustavo Sivieri [UNESP]; Conti, Letícia Citelli [UNESP]; Gomes Filho, João Eduardo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (My University, 2019)
Bioactive materials are constantly indicated in several areas of dentistry in order to induce favorable responses and consequently to modulate/restore the health of tissues that are altered by some pathology. These materials come in direct contact with pulp tissue, bone tissue, cementum, and periodontal ligament. However, the chemical composition of bioactive materials can affect the tissue response and the repair process, as well as compromise systemic health. In this chapter, bioactive material types/indications, systemic changes in the two pathways, and different tissue responses to bioactive materials will be addressed.
Keywords: Endodontic materials; Repair materials; Systemic alteration; Tissue response